Flutuações no mercado de trabalho brasileiro: regiões metropolitanas e não metropolitanas - Kretzmann, Camila Kraide (2007)
The objective this work is to study the fluctuations in the labor market of the regions metropolitans and not metropolitans in the period of 1996 the 2006, or either, to verify which the regions that are creating more jobs, beyond the verification of the existence or not cointegrados movements the series balance jobs, gotten together to the CAGED/MTE for São Paulo, Rio de Janeiro, Minas Gerais, Rio Grande do Sul, Paraná, Bahia, Ceará, Pernambuco and Pará states. The hypothesis is of that the formal labor market comes presenting behavior differentiated between the regions, presenting itself less dynamic in the Brazilian metropolitans. This, in fact, can be evidenced from the theories of regional development, when they initiate in the theories of the localization, they pass for concepts of agglomeration, considered for Marshall (1982), fordist regimen, flexible and, finally, the industrial desconcentration, to give sustentation to the presented hypothesis. On the basis of the methodology of time series, from the cointegration analysis of Engle-Granger and the innovative method of Pesaran et al. (2001), the results, in general, suggest that a relation of balance of long stated period between the regions does not exist metropolitans and not metropolitans for Brazil and the states, with an exception. The methods present resulted that they evidence a relation of long stated period between the regions metropolitan and not metropolitan of Pernambuco, for which is, then, elaborated a error-correction model. Then, the initial hypothesis is confirmed for Brazil and for the majority of the states, when they are analyzed individually. Or either, it has a differential in the behavior of job generation between the metropolitan and not metropolitan region Brazilian and between the regions of the any states.